Analisis Prosedur Pembahasan Rancangan Peraturan Daerah Nomor 10 Tahun 2022 Tentang Penyelenggaraan Perhubungan - Hikmawati, Ikeu; Fitriani, Fingki; Khusnuroja, Rahtiasan; Burhanudin, Ade (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The problem raised in this research is the procedures for drafting  and the procedures for discussing the draft regulations at the discussion stages at levels I and II by the DPRD. This research uses qualitative methods with case study techniques. Data collection using field studies includes observations, interviews and documentation. The selection of informants was carried out purposively and the data results were analyzed interpretively.The research results show the draft proposal came from the executive, namely Dinas Perhubungan, which was then discussed by the DPRD as the legislature in the discussion process at levels I and II so that a mutual agreement was obtained between the Dinas Perhubungan and DPRD that the draft regional regulation was worthy of being declared a regional regulation, to support investment creation and job creation, Regional Regulation no. 10 of 2022 concerning the Implementation of Transportation must be socialized to the public so that it is understood and implemented, it is necessary to make a Keputusan Bupati as a technical guide that specifically discusses parking and railways, there needs to be a compromise between factions so that  community in the administration of transportation are not neglected.